Peningkatan Literasi Keuangan Keluarga Melalui Pencatatan Digital di Komunitas PKK Kelurahan Jatisampurna, Bekasi : Pelatihan Dasar Akuntansi Rumah Tangga Berbasis Aplikasi Android - Alfiana, Alfiana; Awaludin, Dipa Teruna; Ningsih , Titiek Surya; Kusuma, Ema; Tasrim, Tasrim (Prisani Cendekia, 2024)
Financial literacy is an important foundation in realizing sustainable household welfare. In practice, many families, especially those managed by housewives, do not yet have the habit or skills to record and plan expenses systematically. This training aims to improve family financial literacy through digital financial recording education using a simple and easily accessible Android application. The target of the activity is the PKK mothers' community in Jatisampurna Village, Bekasi. The training method is carried out through a participatory approach with stages of identifying needs, compiling modules, direct training, practicing using the application, pre-test and post-test evaluations, and post-training assistance. The results of the activity showed a significant increase in participants' understanding of the basic principles of financial recording and technical skills in using digital applications for household needs. This training also had an impact on changing participants' financial mindsets to be more planned and data-based